Internalization of Lempu' Value in Uncovering the Business Profits of Mixed Traders of Business Ethics Perspectives in Islam - Nani Hamdani Amir; Irwan Misbach; Abdul Wahid Haddade (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to internalize the value of lempu' in uncovering the advantages of mixed traders with Islamic business ethics perspectives. The focus of this research is on the values of lempu' contained in the siri'na pacce culture and the principles of Islamic business ethics. Researchers used qualitative methods with normative ethnographic and theological approaches. Sources of data in this study are primary data obtained directly from the research site with interviews by mixed traders of Bugis-Makassar ethnicity through direct face-to-face. The results explain that the value of lempu' means honesty, truth, sincerity, kindness, and justice shape the character of most of the Bugis-Makassar traders to behave according to their culture. The value of lempu' in the Bugis-Makassar ethnic culture has the same meaning as the principles of Islamic business ethics, namely monotheism, balance, truth, and ihsan. The application of the value of lempu' and the principles of Islamic business ethics in trading yields not only material benefits, but nonmaterial benefits in the form of blessings for peace of mind and does not make it further away from God which brings to the welfare of the world and the hereafter.